Medication Reconciliation in the Hospital: An Interactive Case-Based Session for Internal Medicine Residents - Michael McShane; Rachel Stark (MedEdPORTAL, 2018)
Introduction Medication reconciliation is a complex process of creating and maintaining the most accurate medication list for a patient to help guide therapy. Done incorrectly, the process of medication reconciliation can lead to medical error and result in adverse events for patients. Medication reconciliation on inpatient medicine service is often done by internal medicine residents. However, published reports of educational interventions for residents are limited. Methods We created a 1-hour session that was experiential, case based, and targeted to the level of a first-year resident. In total, 31 internal medicine residents completed the curriculum, which involved either a 1-hour classroom group activity or an individual virtual activity. The curriculum was evaluated using standard forms with qualitative feedback regarding learner satisfaction, pre- and postsession confidence survey, and pre- and postsession patient chart audits. Results Qualitative feedback demonstrated residents' positive experiences. There was no significant change in residents' confidence in portions of the medication reconciliation process. One month following the educational intervention, 100% of inpatient charts audited for review of the medication list were accurate, as compared to 67%-83% accuracy prior to the session. Discussion This novel case-based medication reconciliation teaching session, targeted at learners in an internal medicine residency, can easily be implemented at other institutions using the institution-specific electronic health record. The session was well received by residents, and we observed improved accuracy in the medication reconciliation process done by residents.